MULTILINGUALISM IN SCHOOLS: LITERATURE ANALYSIS OF TEACHING APPROACHES AND METHODS - Yosep Heristyo Endro Baruno; Martoni Meleaki Lely; Yosua Padama (Indonesian Journal of Education (INJOE), 2025)
Multilingualism in education is increasingly becoming a global concern because of its role in improving students' cognitive, academic and social skills. This research is a systematic literature review which aims to analyze various teaching approaches and methods in a multilingual school environment. Various scientific sources, including journal articles, academic books, and research reports, were reviewed to identify the effectiveness and challenges of immersion, translanguaging, bilingual, and plurilingual approaches to learning. The analysis results show that the immersion approach is effective in improving target language skills, while translanguaging is more inclusive in supporting students' academic understanding. Bilingual and plurilingual approaches also offer flexibility in learning, especially in environments with high linguistic diversity. Additionally, technology plays an important role in supporting multilingual learning through interactive tools and digital platforms. However, challenges such as gaps in access to education, stigma against minority languages, and the readiness of teaching staff are still obstacles in implementing multilingualism in schools. This research contributes to providing insight into strategies that can be adopted to optimize multilingual learning, as well as highlighting the need for more inclusive and adaptive education policies. It is hoped that the implications of this study can help educators and policy makers in designing more effective and sustainable multilingual teaching programs.